A global assessment of the degree of price stickiness – results from the NBB business survey - Emmanuel Dhyne (National Bank of Belgium, 2009)
In this paper, we estimate the degree of price stickiness in Belgium using the NBB business survey. Compared to similar empirical exercises based on consumer or producer price data, the micro data set used allows us to cover most of the Belgian economy in one exercise and therefore provides a better estimate of the overall degree of price stickiness. Based on our estimates, 19.2% of prices are changed each month. In the manufacturing sector and the trade sectors, the frequency of price changes is close to 24.5%. In the construction sector the frequency of price changes is close to 20.5% and in the B2B service sectors it is almost 9%. Econometric analyses of the determinants of the sectoral frequency of price changes indicate, on the one hand, that the cost structure is the main explanatory variable of the sectoral discrepancies. On the other hand, we find that domestic competition does not seem to explain an excess or shortage of price changes at the sectoral level
Keywords: D21; D40; 330; price rigidity; frequency of price changes; competition; Preismanagement; Preisrigidität; Branche; Wettbewerb; Belgien